2022
DOI: 10.32479/ijeep.13201
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Development of Kazakhstan’s Raw Material (Oil and Gas) Regions: Multifactorial Model for Empirical Analysis

Abstract: The following paper reveals the applied aspects of multi-factor analysis allowing identifying patterns of innovative development of Kazakhstan’s raw material (oil and gas) regions in connection with modernization transformations. Initial signs of indicators for the period between 2008 and 2020 are currently under investigation using factor analysis. All data have been analyzed with IBM SPSS 23. In considerable detail, authors describe the methodology of this study and provide the results of statistical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the flip side, difficult climatic conditions and the high cost of infrastructure maintenance hinder their sustainable socio-economic development and add to the growth of digital inequality. Our previous research [73] has shown that the results of an analysis of resource-based regions of Kazakhstan indicate a low level of innovation activity, and the instability of regional development. This predetermines the strengthening of the search for factors and new tools and measures to disclose the existing potential and detailed research of open innovation dynamics to create and implement innovation in regions where oil and gas production predominates in the economy.…”
Section: Discussionmentioning
confidence: 99%
“…On the flip side, difficult climatic conditions and the high cost of infrastructure maintenance hinder their sustainable socio-economic development and add to the growth of digital inequality. Our previous research [73] has shown that the results of an analysis of resource-based regions of Kazakhstan indicate a low level of innovation activity, and the instability of regional development. This predetermines the strengthening of the search for factors and new tools and measures to disclose the existing potential and detailed research of open innovation dynamics to create and implement innovation in regions where oil and gas production predominates in the economy.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in technology play a pivotal role in shaping the environmental sustainability of cross-border energy trade [17,18]. The researchers have explored the application of innovative technologies, such as leak detection systems and eco-friendly materials for pipelines, as means to reduce environmental risks [19,20,21]. Integrating such technologies into the infrastructure of the Kazakhstan-China pipeline could be instrumental in preventing and addressing potential environmental incidents [22,23].…”
Section: Technological Innovations For Sustainable Energy Transportationmentioning
confidence: 99%
“…This will help bring the legislation in line with the directives of the European Union and create new mechanisms to support the renewable energy industry. In addition, the financial aspect is also of great importance since the EU will not finance projects related to polluting technologies for the restoration of Ukraine [38], [39], [40], [41].…”
Section: Namementioning
confidence: 99%